(untitled) (Research, Society and Development, 2022)
The Academic Control system (SCA) refers to an information system, used as an academic tool in the relationship between professor and university student, allowing the student to have access to school records, subject grades, certificates, among other procedures. This system provides information that must be accessed easily and efficiently in its operation. A public sector needs to act with precision, presenting an SCA in a satisfactory way, with quality and excellence, meeting the needs of users/target audience. Given the above, this article aims to evaluate the satisfaction of teachers at Campus VII/Patos - PB, UEPB, in relation to the use of the academic system. In terms of methodology, the study presents an applied approach, exploratory research, bibliographic reference, usability of the forms google tool (online form) as an object of data collection, inductive method, and quantitative evaluation. In relation to the form of treatment or interpretation of the data, the Likert scale, the quality parameters of the ISO/IEC 25010:2011 Standard, the explanation of graphs with percentages of the degrees of agreement and tables identifying the average ranking of these levels of agreement were used. for better evaluation of the data obtained. As a result of the research, a favorable result was identified, that is, that the professors of Campus VII/Patos-PB, UEPB, are satisfied with the use of the Academic Control System.